A clinician's guide to ADHD treatment options. Issue 7 (3rd October 2017) - Mattingly, Gregory W; Wilson, Joshua; Rostain, Anthony L
ABSTRACT: Attention deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental condition of children and adolescents that often persists into adulthood. Primary care physicians are commonly the first to diagnosis ADHD and initiate a treatment plan with the patient. Guidelines recommend psychostimulant treatment as a first-line therapy in the management plan because it has a substantial impact on alleviating the core symptoms of ADHD. The recent development of a variety of methylphenidate and amphetamine formulations provides many options to meet individual patient lifestyle needs. Liquid, chewable, sprinkled capsule, wearable patch, and orally disintegrating tablet formulations are currently available for patients who may be noncompliant with or have difficulty swallowing traditional pills. This review provides a resource for physicians to identify the stimulant delivery formulation that best suits the patient. Formulations in development are also discussed.